Simple Periscope To Observe Light Reflecting Off A Flat Mirror - Ziyanti Putri Setia Gandi; Nur Kholisah; Mohammad Danial; Ahmad Suryadi; Fuji Hernawati Kusumah (PT. ALHAFI BERKAH INDONESIA, 2023)
This simple periscope is made as a tool to help students understand the concept of reflection from two flat mirrors, observe the process of forming an image of an object, and observe the process of reflecting light using a laser as a light source on simple periscope props. The first observation by using the periscope directly, the observation results obtained are that it produces right-left images of objects that are not reversed, the images also look upright and virtual. In addition, the size of the image is also the same as the original object. Based on the second observation, specifically observing the process of reflecting light with a laser, where in this second observation there were two reflections of light. The laser light fired at the first flat mirror is reflected straight to the second mirror, then reflected back straight from the second mirror to the outside at the same angle of 45°.